Effect of different number of players and training regimes on physiological and technical demands of ball-drills in basketball - Conte, D.; Favero, T. G.; Niederhausen, M.; Capranica, L.; Tessitore, A. (Journal of Sports Sciences, 2016)
This study aimed to analyse the effects of two factors (number of players and training regimes) on players` physiological and technical demands in basketball ball-drills. Twenty-one young basketball players performed four different ball-drills (two levels for each factor). The number of players involved was 2vs2 and 4vs4, while ball-drill regimes were continuous and intermittent. Physiological demand was assessed using the percentage of maximal heart rate (%HRmax), Edwards` training load and rating of perceived exertion (RPE). Furthermore, the following technical actions were collected: dribbles, steals, rebounds, turnovers, passes (total, correct, wrong and % of correct pass) and shots (total, scored, missed and % of made shot). A 2 × 2 (number of players × regime) two-way ANOVA with repeated measures was applied for physiological parameters and technical actions. The 2vs2 condition showed higher %HRmax (P < 0.001), Edwards` training load (P < 0.001), RPE (P < 0.001), number of dribbles (P < 0.001), rebounds (P < 0.001), passes [total (P = 0.005) and correct (P = 0.005)] and shots [total (P < 0.001) scored (P < 0.001) and missed (P < 0.001)] than 4vs4. Moreover, the continuous regime revealed higher %HRmax (P < 0.001), Edwards` training load (P < 0.001), RPE (P = 0.006) and dribbles (P < 0.001) than the intermittent regime. This study showed that both number of players and regime are useful variables able to modify basketball ball-drills workload.